Anatomy of the Le Fort I segment: Are arterial variations a potential risk factor for avascular bone necrosis in Le Fort I osteotomies?. Issue 8 (August 2018) - Bruneder, Simon; Wallner, Jürgen; Weiglein, Andreas; Kmečová, Ĺudmila; Egger, Jan; Pilsl, Ulrike; Zemann, Wolfgang
Abstract: Purpose: Osteotomies of the Le Fort I segment are routine operations with low complication rates. Ischemic complications are rare, but can have severe consequences that may lead to avascular bone necrosis of the Le Fort I segment. Therefore the aim of this study was to investigate the blood supply and special arterial variants of the Le Fort I segment responsible for arterial hypoperfusion or ischemic avascular necrosis after surgery. Material and methods: The arterial anatomy of the Le Fort I segment's blood supply using 30 halved human cadaver head specimens was analyzed after complete dissection until the submicroscopic level. In all specimens the arterial variants of the Le Fort I segment and also the arterial diameters measured at two points were evaluated. Results: The typical known vascularization pattern was apparent in 90% of all specimens, in which the ascending palatine (D1: 1, 2 mm ± 0, 34 mm; D2: 0, 8 mm ± 0, 34 mm) and ascending pharyngeal artery (D1: 1, 3 mm ± 0, 58 mm; D2: <0, 4 mm) were both supplying the Le Fort I segment. However in 10% of all specimens, the Le Fort I segment was dependent on the ascending pharyngeal artery alone and the missing ascending palatine artery was replaced with the anterior branch of the ascending pharyngeal artery (D1: 1, 9 mm ± 0, 32; D2: 1, 0 mm ± 0, 3 mm). Conclusion: This study is the first description of a special type of arterial variation of the Le Fort I segment. The type of this arterial variation, its clinical relevance and potential consequences are explained. Individuals with this special arterial anatomy may clinically be at a high risk for hypoperfusion and avascular segment necrosis after surgery. An individualized operation plan may prevent ischemic complications in at-risk patients.